KEY TYPES OF ACADEMIC TEXTS IN JAPANESE-LANGUAGE JOURNALS - Aragão, Rodrigo Moura Lima de (The ESPecialist, 2018)
Little is known about the types of academic texts published in Japanese journals—except for ronbun (the Japanese scholarly article or paper). This paper sheds some light on the issue by reporting results of an analysis of documents from 88 journals on J-Stage (Japan Science and Technology Information Aggregator, Electronic), a free-access, multidisciplinary, electronic collection of Japanese academic publications. The first step in the process was to find frequent designations in the documents, which were considered clues to chief types of texts. The next step was to describe how Japanese journals conceive the types previously identified. This was done by collecting, translating, and summarizing explanatory excerpts about them. The results may serve as points of departure for including Japanese academic writing in the teaching of Japanese.